Pharmacokinetic and pharmacodynamic interactions between metformin and a novel dipeptidyl peptidase-4 inhibitor, evogliptin, in healthy subjects - Rhee SJ; Choi Y; Lee S; Oh J; Kim SJ; Yoon SH; Cho JY; Yu KS (Dove Medical Press, 2016)
Su-jin Rhee,1,* YoonJung Choi,1,* SeungHwan Lee,1,2 Jaeseong Oh,1 Sung-Jin Kim,3 Seo Hyun Yoon,1 Joo-Youn Cho,1 Kyung-Sang Yu1 1Department of Clinical Pharmacology and Therapeutics, Seoul National University Hospital, Seoul National University College of Medicine, Seoul, Republic of Korea; 2Clinical Trials Center, Seoul National University Hospital, Seoul, Republic of Korea; 3Department of Clinical Development, Dong-A ST Co., Ltd., Seoul, Republic of Korea *These authors contributed equally to this work Abstract: Evogliptin is a newly developed dipeptidyl peptidase-4 (DPP-4) inhibitor, which is expected to be combined with metformin for treating type 2 diabetes mellitus. We investigated the potential pharmacokinetic and pharmacodynamic interactions between evogliptin and metformin. A randomized, open-label, multiple-dose, six-sequence, three-period crossover study was conducted in 36 healthy male subjects. All subjects received three treatments, separated by 7-day washout intervals: evogliptin, 5 mg od for 7 days (EVO); metformin IR, 1,000 mg bid for 7 days (MET); and the combination of EVO and MET (EVO + MET). After the last dose in a period, serial blood samples were collected for 24 hours for pharmacokinetic assessments. During steady state, serial blood samples were collected for 2 hours after an oral glucose tolerance test, and DPP-4, active glucagon-like peptide-1, glucose, glucagon, insulin, and C-peptide were measured to assess pharmacodynamic properties. EVO + MET and EVO showed similar steady state maximum concentration and area under the concentration–time curve at steady state values for evogliptin; the geometric mean ratios (90% confidence interval) were 1.06 (1.01–1.12) and 1.02 (0.99–1.06), respectively. EVO + MET slightly reduced steady state maximum concentration and area under the concentration–time curve at steady state values for metformin compared to MET, with geometric mean ratios (90% confidence interval) of 0.84 (0.79–0.89) and 0.94 (0.89–0.98), respectively. EVO + MET and EVO had similar DPP-4 inhibition efficacy, but EVO + MET increased active glucagon-like peptide-1 and reduced glucose to larger extents than either EVO or MET alone. Our results suggested that EVO+MET could provide therapeutic benefits without clinically significant pharmacokinetic interactions. Thus, the EVO + MET combination is a promising option for treating type 2 diabetes mellitus. Keywords: type 2 diabetes, drug interaction, DA-1229, DPP-4 inhibitor, OGTT